2018
DOI: 10.12957/demetra.2018.27515
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Perfil Nutricional E Qualidade De Vida Após Realização De Cirurgia Bariátrica Em Um Hospital Público De Goiânia, Brasil

Abstract: Objetivo: avaliar o perfil nutricional e qualidade de vida de indivíduos submetidos a cirurgia bariátrica em um hospital público de Goiânia. Metodologia: Estudo transversal, realizado entre agosto a novembro de 2016, com 56 pacientes do ambulatório de obesidade com 6, 12 e 18 meses de pós-operatório de bypass gástrico em Y de Roux. Analisaram-se perfil antropométrico, presença de comorbidades, hábitos de vida e qualidade de vida por meio do instrumento BAROS. Resultados: 84% do sexo feminino, com média de idad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
(13 reference statements)
0
6
0
1
Order By: Relevance
“…The result showed that 27% of patients rated their quality of life as improved and 73% as greatly improved. No individual considered the quality of life unchanged or worsened by this parameter [27].…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that 27% of patients rated their quality of life as improved and 73% as greatly improved. No individual considered the quality of life unchanged or worsened by this parameter [27].…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted on bariatric surgery highlight that women are the majority in the search for surgery [15][16][17][18] and the prevalence of BED 6,[19][20][21] . This can be explained by the greater influence of body and beauty ideals that women are subject to and the cultural influence of the subjective female constitution 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The scores of each domain are multiplied by a factor that represents their influence and then added, reaching the total score. The factor is 0.6 for desire (1,2), 0.3 for arousal (3,4,5,6) and lubrication (7, 8, 9, 10) and 0.4 for orgasm (11,12,13), satisfaction (14,15,16) and pain (17,18,19). The value of the scores for each domain ranges from 0 to 6 (except desire, for which the minimum is 1.2, and satisfaction, for which it is 0.8) and the total score ranges from 2 to 36.…”
Section: 564337)mentioning
confidence: 99%
“…The other items -physical activity, social relationship, work performance and sexual interest -can each go up to 0.5 point (Much less = -0,5; Less = -0.25; The same = 0; More = +0,25; Much more = +0,5). In the analysis of the final score, the results can be classified as "Insufficient", "Moderate", "Good", "Very good" and "Excellent" 13 . The final quality of life assessment results in a numerical value between -3 and + 3.…”
Section: 564337)mentioning
confidence: 99%
See 1 more Smart Citation